Barriers to Initiation of Pediatric HIV Treatment in Uganda: A Mixed-Method Study - Boender, T. Sonia; Sigaloff, Kim C. E.; Kayiwa, Joshua; Musiime, Victor; Calis, Job C. J.; Katumba, Lillian Nakatudde; Khauda, Elizabeth; Mukuye, Andrew; Ditai, James; Mugyenyi, Peter; Rinke deWit, Tobias F.; Kityo, Cissy (AIDS research and treatment, 2012)
Although the advantages of early infant HIV diagnosis and treatment initiation are well established, children often present late to HIV programs in resource-limited settings. We aimed to assess factors related to the timing of treatment initiation among HIV-infected children attending three clinical sites in Uganda. Clinical and demographic determinants associated with early disease (WHO clinical stages 1-2) or late disease (stages 3-4) stage at presentation were assessed using multilevel logistic regression. Additionally, semistructured interviews with caregivers and health workers were conducted to qualitatively explore determinants of late disease stage at presentation. Of 306 children initiating first-line regimens, 72% presented late. Risk factors for late presentation were age below 2 years old (OR 2.83, ), living without parents (OR 3.93, ), unemployment of the caregiver (OR 4.26, ), lack of perinatal HIV prophylaxis (OR 5.66, ), and high transportation costs to the clinic (OR 2.51, ). Forty-nine interviews were conducted, confirming the identified risk factors and additionally pointing to inconsistent referral from perinatal care, caregivers’ unawareness of HIV symptoms, fear, and stigma as important barriers. The problem of late disease at presentation requires a multifactorial approach, addressing both health system and individual-level factors.